Study of the Results of the Department of Transportation Employee Training Needs Analysis At Bekasi College of Land Transportation - Sarwandi Sarwandi (Empowerment : Jurnal Ilmiah Program Studi Pendidikan Luar Sekolah, 2020)
Training Needs Analysis (TNA) is the initial and strategic step in the implementation of training programs, so special attention needs to be paid to management. This research was developed to see the results of the analysis of the training needs of the transportation agency staff conducted by the Bekasi College of Land Transportation in order to get an overview in preparing education and training programs. The method used is case study. The analysis is organizational level analysis, operational level analysis, and individual level analysis to get training participants who are in line with agency / agency needs in improving the performance and quality of training. The results of the training needs analysis conducted on 521 transportation agencies were obtained data from the transportation agency that sent 52 forms provincial and city / regency transportation agencies, with 179 candidates for 11 types of training. From the number of training programs that will be implemented, the training participants are more likely to choosemotor vehicle testing training .